Stability regions for an explicit numerical solution of the one-dimensional richards equation applied to water soil infiltration - Pedrozo, Héctor Alejandro (2022)
Fil: Pedrozo, Héctor Alejandro. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto de Materiales de Misiones; Argentina.